2021
DOI: 10.3389/fpls.2021.658777
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Growth Increments Reveal Local and Regional Climatic Signals in Two Pinus pinaster Populations

Abstract: Tree rings are valuable proxies of past climate that allow inferring past growth responses to climate variability and extreme events, which is only possible considering that the relationship between tree growth and environmental conditions is linear and stable over time. However, in the last decades, divergent growth patterns have been observed in trees from the same forest stand, while unprecedented growth convergence was observed between trees from distant locations. Here, we use a new approach that consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The multiscalar SPEI could represent the different effects of water availability on tree growth in particular periods/seasons in tree-ring analyses and might cause different responses during drought reconstructions. It is important to choose the appropriate SPEI timescales [38,39]. To identify the major environmental signals that influence tree growth, the SPEI at the 1-month scale was used to estimate additional variations in drought.…”
Section: Climatic Datamentioning
confidence: 99%
“…The multiscalar SPEI could represent the different effects of water availability on tree growth in particular periods/seasons in tree-ring analyses and might cause different responses during drought reconstructions. It is important to choose the appropriate SPEI timescales [38,39]. To identify the major environmental signals that influence tree growth, the SPEI at the 1-month scale was used to estimate additional variations in drought.…”
Section: Climatic Datamentioning
confidence: 99%
“…As mentioned earlier, a higher rate of change could take place at altitudes far higher than the meteorological stations, but the divergence could also be compounded by a prolongation of the growing season [96]. The earlier warming of spring can trigger an earlier start of cambial activity and support wider tree-ring widths [96]. The remoteness of the sampled areas likely precludes substantial anthropogenic disturbances, which could also foster increased growth rates not explained by temperatures alone.…”
Section: Comparisons Between Himalayan and Northern Hemisphere Temper...mentioning
confidence: 94%
“…Contrastingly, the divergence problem in this study differs from high latitudes of the North, with decreasing observed temperature and rising NB-TEMR values after 2010 (Figure 7). As mentioned earlier, a higher rate of change could take place at altitudes far higher than the meteorological stations, but the divergence could also be compounded by a prolongation of the growing season [96]. The earlier warming of spring can trigger an earlier start of cambial activity and support wider tree-ring widths [96].…”
Section: Comparisons Between Himalayan and Northern Hemisphere Temper...mentioning
confidence: 97%
“…Concurrently, forest growth or development can also spontaneously reduce tree size heterogeneity. At lower elevations, increased precipitation can promote radial growth by reducing water stress and accelerating xylem activity during the growing season (Vieira et al 2021). This boost will be more pronounced for smaller trees that grow faster, thus reducing CVR.…”
Section: Limited Influence Of Climate On Tree Size Heterogeneity Of S...mentioning
confidence: 99%